Modelo experimental de diabetes mellitus e doença renal associados em camundongos - Silva, Pâmela Henrique (2022)
Chronic non-communicable diseases such as Diabetes Mellitus (DM), affect an important part of the population. DM is a lipoprotein metabolic disorder, characterized by hyperglycemia, resulting from an insufficient or deficient secretory response of the hormone insulin, and is still one of the main causes of Kidney Disease (KD). Given the severity of the microvascular complications caused by DM, as well as, cardiomyopathy, encephalopathy, retinopathy, neuropathy and nephropathy, this study was justified. The aim of this study was to associate the models of DM and KD in mice. Sixty-four adult female mice (Mus musculus) of the Swiss strain were used, weighing approximately 20 g, were divided groups: G1, control (n=32) and G2, associated diseases (n=32). First the G2 animals were induced to arteriovenous stenosis (ischemia, 10 minutes and reperfusion) of the left kidney, being observed for 14 days, before receiving streptozotocin (STZ and diet. After this period, STZ was administered at a dose of 150 mg/kg, intraperitoneally, and aqueous glucose solution (10%), for 24 hours, followed by a high-fat diet for 7 days. The evolution of KD was observed using a urine analysis test strip and DM by analyzing blood glucose on a digital glucose monitor. Ischemia and reperfusion were verified by observing changes in color during surgery, volume and size of the left kidney, when compared to the contralateral kidney. Initial renal alterations were observed in G2, in the first 14 days, increased urinary density, pH alteration, presence of glucose, proteins and leukocytes, when compared to G1. DM was confirmed by the presence of hyperglycemia, starting at 200 mg/dL, on the 7th day of induction. G2 animals showed constant weight loss when compared to G1. It was possible to induce and confirm associated DM and KD, with low mortality and easy execution.